(untitled) (The Peerian Journal, 2022)
As a result, our country has become an integral part of our national and national values of the importance and importance of self-esteem in our country. On March 24, 1997, all specialist and multilateral organizations have been able to reduce the incentives for the moral and intellectual aspect of the field of journalism as "The Basics of Human Rights". Because national and universal values were not recognized, the colonists had no morality to perfection. In addition, in our study, our students studied the spirit of spirituality and national values in general and the generalization of the students’ appreciation of the influence of morality forming.